Scientific zero to one: Some common properties of highly-influential papers - Jahani Yekta, Mohammad Mahdi (Malaysian Journal of Library and Information Science, 2021)
Based on an intensive study of the most popular papers of the approximately 6,000 top-1% highly-cited (HC) researchers 2018 announced by Clarivate Analytics, the most HC papers in different fields of science in the interval 2001-11 reported by Web-of-Science (Thomson- Reuters), the top 100 most-HC ones ever; reported in 2014 by the same institute, and also the scientific backgrounds and career trends of the involved authors, we first analyze several major properties common in most such highly-influential papers that add something fundamentally new to their corresponding fields, taking them from a “zero” state in some domain to “one”. These properties include importance of the paper topic in essence, firsthand approach to the problem it focuses on, notable improvement of the solution it offers for the problem compared to its existing counterparts, monopoly in some aspect, durability, proper timing, knowledgeable research team and availability of the required resources, effective presentation to the right audience, and; finally, perseverance. We next propose soft citation; an upgrade to the current citation standards, and then a problem-oriented interactive research model as a transformative complement for the state-of-the-art academic publishing system, that would expedite this zero to one transition.